Pengaruh Penempatan Penghalang Berbentuk Segitiga di Depan Silinder dengan Variasi Kecepatan Aliran Udara terhadap Koefisien Drag - Tista, Si Putu Gede Gunawan; Suriadi, I Gusti Agung Kade; Astawa, Putu Pageh (Rekayasa Mesin, 2015)
One of the ways to preserve energy on the air plane is by decreasing the drag. Drag is closely related to the flow separation, the faster the separation, then the drag will increase more. Because of that, efforts were conducted to decrease drag is by manipulating a fluid flow field that is by installing triangle rod obstacle in front of the cylinder. The purpose of this research is to analyze the effect of installing triangle rod obstacle in front of the cylinder by various air flow velocity on the drag cofficient. In this research, the experiment was conducted in the wind tunnel, which consists of blower, pitot pipe, manometer, cylinder pipe, and triangle rod. The air flow velocity was varied from 6.25 m/s, 5.01 m/s, 4.09 m/s, 3.17 m/s, 2.24 m/s .The Reynold number based on cylinder (D = 42 mm) and air flow velocity is Re =18.100, 14.500, 11.800, 9.170, 6.480 .The distance triangle rod and cylinder is L = 70 mm or L/D=1.67.Pressure distribution is achieved by measuring the cylinder surface on 36 spots with interval of 100. The measured data was pressure of cylinder surface, static pressure, and airflow speed. The research results showed that the triangle rod could decrease the drag of cylinder. Coefficient drag for cylinder without triangle rod was 0,1276 while the less triangle rod was 0,01882 which takes place at speed 6,2479 m/s.